"The Most Wonderful Collection of Original Documents in the United States": Notes on the Lives and Work of Two New Orleans Translators. Issue 3 (June 2015) - Forsythe, Jenny Marie; Tucker, Susan
Heloise Hulse Cruzat (1862–1931) and Laura Louise Porteous (1875–1952) worked in New Orleans during the first half of the twentieth century to transcribe, translate, and index the Louisiana Historical Society's (LHS) vast collection of French and Spanish colonial judicial records. This essay places the body of their work for the LHS in national perspective, describes their lives in the context of evolving roles for women in New Orleans cultural institutions, and considers the significance of their work for past and future scholars.1